IoT-Based Smart Door Lock System with Fingerprint and Keypad Access - Permana, Ketut Ananta Kevin; Piarsa, I Nyoman; Wiranatha, Anak Agung Ketut Agung Cahyawan (Journal of Information System and Informatics, 2024)
Doors are important components in a home, serving as entry points, room dividers, and security barriers. Door locks have evolved from manual mechanisms to automatic systems using technologies such as passwords, face sensors, and fingerprint sensors. To enhance practicality and efficiency, an Internet of Things (IoT)-based Smart Door Lock system using keypads and fingerprint sensors was developed in this research. The system was built using the Waterfall model Software Development Life Cycle (SDLC) and utilizes Firebase for real-time data communication and control through an Android application. Black box testing was conducted to verify the system’s functionality, achieving a 100% success rate across 20 trials. The system offers enhanced security and remote access control, with potential applications in both residential and commercial settings.